Homeodomain-Interacting Protein Kinase-2: A Critical Regulator of the DNA Damage Response and the Epigenome - Kuwano, Yuki (Int J Mol Sci, 2016)
Homeodomain-interacting protein kinase 2 (HIPK2) is a serine/threonine kinase that phosphorylates and activates the apoptotic program through interaction with diverse downstream targets including tumor suppressor p53. HIPK2 is activated by genotoxic stimuli and modulates cell fate following DNA damage. The DNA damage response (DDR) is triggered by DNA lesions or chromatin alterations. The DDR regulates DNA repair, cell cycle checkpoint activation, and apoptosis to restore genome integrity and cellular homeostasis. Maintenance of the DDR is essential to prevent development of diseases caused by genomic instability, including cancer, defects of development, and neurodegenerative disorders. Recent studies reveal a novel HIPK2-mediated pathway for DDR through interaction with chromatin remodeling factor homeodomain protein 1γ. In this review, we will highlight the molecular mechanisms of HIPK2 and show its functions as a crucial DDR regulator.